Towards a sustainable ecology : Global Challenges and Local Responses in Africa and Asia - (:unkn) unknown (My University, 2012)
55 years after the 1955 Bandung Asian-African Conference and 20 years after the end of the Cold War, in the context of Globalisation, the world is still characterised by wars, domination by the powerful, exploitation of the weak. In addition, Globalisation has posed two challenges for the sustainability of our planet: the degradation of Environment and the growth of Cities. People cannot escape from these two global challenges, but face them in their own localities. The actors for a sustainable future are therefore supposed to answer the “Global Challenges” with “Local Responses”. The responses from Africa and Asia deserve special attention. On the one hand, despite the continuous process of globalisation following the expansion of capitalism, colonialism and imperialism started from Europe, Africa and Asia have not been uprooted by Western Civilisation and are therefore thought to be the source and pool of bio- and cultural diversity needed for the sustainability of our planet. On the other hand, Africa and Asia are particularly affected by the degradation of Environment and the growth of Cities. The planet is in the midst of a 6th great extinction of life forms faster than the previous ones and the climate change largely provoked by the “developed North” will be especially harmful to the “developing South”. As for Citification, the urban population worldwide grew over 10-fold during the 20th century alone, and UN has projected in 2012 that “Africa and Asia together will account for 86 per cent of all growth in the world’s urban population over the next four decades.” So, what are the “Local Responses” from Africa and Asia to these “Global Challenges”? 29 authors from 16 countries of Africa, Asia, America and Europe try to answer the question: Albinus Mkota Pastory Makalle (Tanzania), Benny Teh Cheng Guan, Ibrahim Abu Bakar (Malaysia), Carina America, Martina Jordaan (South Africa), Darwis Khudori (Indonesia/France), Dede
Keywords: African Research